Abundant tumor promoting stromal cells in lung adenocarcinoma with hypoxic regions. (January 2018) - Nakamura, Hiroshi; Ichikawa, Tomohiro; Nakasone, Shoko; Miyoshi, Tomohiro; Sugano, Masato; Kojima, Motohiro; Fujii, Satoshi; Ochiai, Atsushi; Kuwata, Takeshi; Aokage, Keiju; Suzuki, Kenji; Tsuboi, Masahiro; et al.
Highlights: Carbonic anhydrase IX (CAIX) is a hypoxia marker. Expression of CAIX by cancer associated fibroblasts (CAFs) is associated with poor prognosis of lung adenocarcinoma. The presence of abundant tumor promoting stromal cells is characteristic of lung adenocarcinoma with hypoxic regions. Impact of hypoxic microenvironment on the tumor progression may be explained by the abundant tumor promoting stromal cells. Abstract: Objectives: Carbonic anhydrase IX (CAIX) is a marker of hypoxia and its expression by cancer associated fibroblasts (CAFs) was reportedly associated with the poor prognosis of lung adenocarcinoma. This study aimed to characterize the hypoxic microenvironment containing CAIX (+) CAFs. Materials and methods: First, we evaluated the clinicopathological significance of CAIX expression by CAFs in 3 cm and above lung adenocarcinoma (n = 188). We then compared the expressions of E-cadherin, ezrin, ALDH-1, CD44, EGFR, HSF-1, Glut-1, and PD-L1 in cancer cells, as well as those of CD204 and podoplanin in stromal cells between CAIX (+) CAFs and CAIX (−) CAFs cases (n = 25, each). Results: In total, 48 patients had CAIX (+) CAFs (26%). Multivariate analysis revealed that CAIX expression by CAFs could serve as an independent unfavorable prognostic factor for recurrence-free survival (p < 0.05). The staining score of hypoxia marker Glut-1 in cancer cells was significantly higher in cases with CAIX (+) CAFs than in those with CAIX (−) CAFs (median: 20 vs. 0, p < 0.01). In addition, the numbers of CD204 (+) tumor-associated macrophages (TAMs) and podoplanin (+) CAFs were significantly higher in the CAIX (+) CAFs group than in the CAIX (−) CAFs group (TAMs: 31.5 vs. 17.0: p < 0.01, CAFs: 20 vs. 0: p < 0.05). The staining score of the other markers did not differ between the groups. Conclusion: Our results indicate that the presence of abundant tumor promoting stromal cells, CD204 (+) TAMs, and podoplanin (+) CAFs is characteristic of the tumor microenvironment containing CAIX (+) CAFs, which contributes to an increase in aggressive behavior in lung adenocarcinoma with hypoxic regions.